2000
DOI: 10.1159/000025959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intrarenal Infusion of Angiotensin–(1–7) in the Dog

Abstract: Angiotensin–(1–7), (Ang–(1–7)), a metabolite of Ang II and /or Ang I, was infused into the renal artery (i.r.a) of anesthetized dogs in order to demonstrate its possible direct renal action. The dose administered, 15 Ìg/kg BW/min in isotonic saline (0.072 ml/kg BW/min) throughout the experiment, did not influence the systemic arterial pressure and water and sodium excretion from the contralateral noninfused kidney. Renal blood flow (RBF) was measured by an electromagnetic flowmeter, glomerular filtration rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
5
32
0
1
Order By: Relevance
“…It is of particular interest that kidney ACE2 activity and Ang-(1-7) levels after clipping significantly increased in the nonclipped kidneys of 2K1C hypertensive rats. These findings support the notion that Ang-(1-7) serves as physiological endogenous antagonist, which in many instances opposes the AT 1 receptor-mediated vasoconstrictor and antinatriuretic actions of Ang II [4][5][6]17,18,[32][33][34][35]. Moreover, our findings that chronic Ang-(1-7) receptor blockade by [7-D-Ala] elicited a significant decrease in RPF in 2K1C rats support the notion derived from our previous study evaluating the effects of acute intrarenal Ang-(1-7) receptor blockade, namely that Ang-(1-7) acts as an important vasodilator and endogenous paracrine natriurectic factor; this might contribute to sustain renal hemodynamics and to attenuate the level of hypertension in 2K1C Goldblatt hypertensive rats [12].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is of particular interest that kidney ACE2 activity and Ang-(1-7) levels after clipping significantly increased in the nonclipped kidneys of 2K1C hypertensive rats. These findings support the notion that Ang-(1-7) serves as physiological endogenous antagonist, which in many instances opposes the AT 1 receptor-mediated vasoconstrictor and antinatriuretic actions of Ang II [4][5][6]17,18,[32][33][34][35]. Moreover, our findings that chronic Ang-(1-7) receptor blockade by [7-D-Ala] elicited a significant decrease in RPF in 2K1C rats support the notion derived from our previous study evaluating the effects of acute intrarenal Ang-(1-7) receptor blockade, namely that Ang-(1-7) acts as an important vasodilator and endogenous paracrine natriurectic factor; this might contribute to sustain renal hemodynamics and to attenuate the level of hypertension in 2K1C Goldblatt hypertensive rats [12].…”
Section: Discussionsupporting
confidence: 83%
“…This view is also supported by a previous study showing that vasodilator and BP-lowering responses to Ang-(1-7) are more pronounced in 2K1C hypertensive dogs than in sham-operated dogs [36]. Furthermore, our findings that chronic ACE2 inhibition prevented any increase in intrarenal Ang-(1-7) levels, substantially reduced renal hemodynamics and aggravated hypertension in 2K1C hypertensive rats support the view that Ang-(1-7) is an important endogenous agent counterbalancing the renal vasoconstrictor and natriuretic actions of Ang II [4][5][6]17,18,27,28,[32][33][34][35]. In addition, our results show that chronic treatment with ACE2 in 2K1C hypertensive rats was associated not only with reduction of intrarenal Ang-(1-7) levels but also with significant increases in intrarenal Ang II levels.…”
Section: Discussionsupporting
confidence: 82%
“…As previously reviewed elsewhere [8], Ang-(1-7) induces vasodilation and thus an increase in blood flow and a fall in blood pressure. Some studies using higher doses of Ang-(1-7) reported a minor vasoconstrictor effect [9,10], probably as a result of weak AT 1 R stimulation by higher doses of Ang-(1-7). Despite a large number of animal studies, very few human studies on the vascular effects of Ang-(1-7) have been performed.…”
Section: Key Pointsmentioning
confidence: 99%
“…The most important pathway is the cleavage of phenylalanine from the Ang II-molecule by a homolog of ACE, ACE2 [5]. Next to this process, several other pathways lead to the production of Ang- (1)(2)(3)(4)(5)(6)(7), that is, breakdown of Ang I by ACE2 and neutral endopeptidase into the biologically active angiotensin- (1)(2)(3)(4)(5)(6)(7)(8)(9), which on its turn is cleaved into Ang-(1-7) by ACE. In addition, Ang-(1-7) is produced directly out of Ang I by several endopeptidases in the vascular wall [3].…”
Section: Introductionmentioning
confidence: 99%
“…The vasodilator properties of Ang-(1-7) are best demonstrated in situations in which the RAS is activated, such as sodium-volume depletion [20,21], two-kidney one-clip hypertension [22] and [mRen2]27 transgenic hypertensive rats. In isolated precapillary resistance vessels, piglet pial arterioles, the renal glomeruli, aorta and canine coronary arteries, Ang-(1-7) increases lumen diameter at doses equivalent to Ang II-induced contractions [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The lower vasodilator dose threshold obtained in isolated perfused arterial vessels suggests that Ang-(1-7) is acting as a local modulator of vascular tone [31].…”
Section: The Ying-yang Functions Of Ang II and Ang-(1-7)mentioning
confidence: 99%